Answer :

Given,

B = C


AB = AC


To Prove: BQ = CP


Proof: In ABQ and ACP


B = C (Given)


AB = AC (Given)


A = A (Common)


Hence, by A.S.A. Theorem


ABQ ACP


BQ = CP (By c.p.c.t)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Revision on Angle sum Property of TrianglesRevision on Angle sum Property of TrianglesRevision on Angle sum Property of Triangles44 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In two triangles RD Sharma - Mathematics

<span lang="EN-USRS Aggarwal & V Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal & V Aggarwal - Mathematics

In triangle ABC aRD Sharma - Mathematics

In triangles ARD Sharma - Mathematics

ABC is an RD Sharma - Mathematics

In two triangles RD Sharma - Mathematics

If Δ ABCRD Sharma - Mathematics

In Fig. 10.134, iRD Sharma - Mathematics

In triangles ARD Sharma - Mathematics